Customers’ perceptions of Islamic hire-purchase facility in Malaysia: an empirical analysis - Dusuki, Asyraf Wajdi; Abdullah, Nurdianawati Irwani (The International Islamic University Malaysia, 2006)
One of the latest innovative products of Islamic banks is the Islamic hirepurchase facility or Al-IjOErah Thumma al-Bayc (AITAB) which is designed to meet the current demand and avoid certain risks in the financing of consumer durables and motor vehicles. AITAB can be utilized to finance a wide range of assets, either for individual or corporate customers. This paper presents empirical evidence on the customers’ perception of AITAB. A country-wide questionnaire survey has been conducted on 203 AITAB customers, aiming at eliciting their awareness and perception of AITAB facility. Overall, the results provide a strong signal to the bankers that efforts need to be intensified in educating the public about the distinctive characteristics of AITAB and how it may suit the interest of customers in financing their assets. There is a huge potential for AITAB to be marketed to various segments of customers comprising those who are concerned with the legitimacy of the facility, and those who seek convenience and less complicated transactions.